How to assess doctors and health professionals - Davis, Mike, 1947- (Wiley Blackwell, 2013)
This important book offers an introduction to the theory and the varying types of assessment for health care professionals. The book includes information on such topics as Where have work based assessments come from?; Why do we have different parts to the same exam like MCQs and OSCEs?; How do colleges decide who has passed or not?; Why can people pick their own assessors for their MSF?; The role of formative assessment Portfolios and their value. The book avoids jargon, is clear and succinct, and gives the pros and cons of the different assessment processes.